(untitled) (Eduscotech, 2023)
This study aims to assess the effectiveness of project-based learning activities in developing students’ environmental awareness at Kediren 1 Public Elementary School (SDN). Project-Based Learning (PBL) is an approach that provides students with the opportunity to directly engage in research or practical activities related to real-world problems, thereby increasing their understanding and awareness of environmental issues. This study used a quantitative approach with an experimental design, in which two groups of fifth-grade students at SDN Kediren 1 served as the subjects. The experimental group received project-based learning focused on environmental topics, while the control group underwent conventional learning. Data were collected through an environmental awareness questionnaire administered before and after the treatment. The results showed a significant increase in students’ environmental awareness in the experimental group compared to the control group. The t-test results showed a p-value <0.05, indicating that project-based learning can effectively increase students’ environmental awareness. This study recommends implementing project-based learning as a method that can be used to increase students’ environmental awareness in elementary schools.